2nd National Congress of Oncology of Associação Presente: precision and humanization medicine in coping with cancer were the themes of the 2nd National Congress of Oncology Priscila Bernardina Miranda Soares, Cristina Andrade Sampaio - Bernardina Miranda Soares, Priscila; Andrade Sampaio, Cristina (Revista Unimontes Científica, 2020)
2nd National Congress of Oncology of Associação Presente: precision and humanization medicine in coping with cancer were the themes of the 2nd National Congress of Oncology Priscila Bernardina Miranda Soares, Cristina Andrade Sampaio